2016
DOI: 10.1001/jamapediatrics.2016.2023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Variability in Inhaled Nitric Oxide Use and Pulmonary Hypertension in Patients With Congenital Diaphragmatic Hernia

Abstract: for the Congenital Diaphragmatic Hernia Study Group IMPORTANCE Inhaled nitric oxide (iNO) is an expensive, commonly used therapy among patients with congenital diaphragmatic hernia (CDH); however, data to support its ongoing use in this patient population are lacking. OBJECTIVE To describe the spectrum of iNO use among patients with CDH and its association with pulmonary hypertension (pHTN) and mortality. DESIGN, SETTING, AND PARTICIPANTSA review was conducted of prospectively collected patient data in the Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 25 publications
2
64
0
2
Order By: Relevance
“…We found that the right ventricle of Pbx1/2-CKO mice was hypertrophied by P10 compared with that observed in control mice, while the left ventricle was similar in thickness at that stage ( Figure 2J). Patients with CDH often have constricted pulmonary vessels that do not relax normally after birth (8)(9)(10)(11)40). We hypothesized that in the Pbx-mutant model of CDH, deletion of Pbx1/2 might impair the normal VSM relaxation process.…”
Section: Pbx1 Is Expressed Throughout the Embryonic Lung Mesenchymementioning
confidence: 99%
See 2 more Smart Citations
“…We found that the right ventricle of Pbx1/2-CKO mice was hypertrophied by P10 compared with that observed in control mice, while the left ventricle was similar in thickness at that stage ( Figure 2J). Patients with CDH often have constricted pulmonary vessels that do not relax normally after birth (8)(9)(10)(11)40). We hypothesized that in the Pbx-mutant model of CDH, deletion of Pbx1/2 might impair the normal VSM relaxation process.…”
Section: Pbx1 Is Expressed Throughout the Embryonic Lung Mesenchymementioning
confidence: 99%
“…Infants with CDH and PH do not respond consistently to treatment with pulmonary vasodilating medications (8)(9)(10)(11)40). Identifying the basis of this variation has been a major challenge in CDH treatment.…”
Section: Mesenchymal Deletion Of Pbx1/2 Alters the Expression Of Multmentioning
confidence: 99%
See 1 more Smart Citation
“…Echocardiography was carried out in 85% of patients, although the timing of the examination and findings are not presented. Treatment of pulmonary hypertension (mostly inhaled nitric oxide) was employed in 36% of the cohort and in only 48% antenatally diagnosed CDH which is less than the International CDH Study group registry data 2. Extracorporeal membrane oxygenation (ECMO) was only used in 4% which is also significantly lower than the registry 3.…”
mentioning
confidence: 95%
“…Most probably, physicians’ motivation to normalize physiology prevails when faced with a hypoxic ventilated CDH baby. As this treatment is hugely expensive and potentially harmful (35), further studies should aim to evaluate its efficacy and standardize its application in order to optimize patient outcomes and ensure cost-effective practices.…”
Section: Discussionmentioning
confidence: 99%